The popular press and its public in China - Lee, Hsiao-wen (Javnost (Ljubljana), 2010)
The result of media reform in China has led to the profit-driven popular press, instead of the Party press, developing rapidly and heavily influencing the public life in the country. How do the people negotiate with the political power and form their own "public" in daily life through reading the popular press? On the one hand, as the ordinary Chinese people keep their distance from public affairs, they fail to respond to the coverage that is always controlled by the power of the state; this leads to people's dissent from or indifference to the headlines or important news in the popular press. On the other hand, compared with the stuff y and always-positive news of propaganda that is far from their daily lives, trivial news happens under circumstances that are more sensible and meaningful for them. People refer to their reason and sense in daily life to criticise what the truth is. In the meantime, the "public" is aroused through controversy and disagreement.
Keywords: Kitajska; mass media; množični mediji; printing; tisk; svoboda tiska; vladni nadzor; politični vplivi; javnost